Studies in Family Planning - Odeh Amarin, Zouhair (IntechOpen, 2022)
Globally, there is a shortage of family planning services. This shortage is associated with unacceptably high rates of maternal and perinatal morbidity and mortality that are mostly preventable. The current situation does not comply with the United Nations Millennium Declaration, signed in September 2000. Family planning needs to be widely available and easily accessible. In addition, it is vital that research intensifies to further cover the safety, effectiveness, affordability, and acceptability of family planning methods and accessibility to family planning services. This book is designed as an additional contribution to the family planning spectrum. It covers some aspects of family planning and deals with a number of issues that pertain to reproductive health.